A Pragmatic Analysis of Deixis in Billie Eilish's Song Lyrics "Happier Than Ever" - Adelia Maha Suci; Linda Farida Aslamiyah (LINGUISTICA, 2025)
This pragmatics study aims to examine the use of deixis in Billie Eilish’s song “Happier Than Ever,” focusing on its role in shaping emotional dynamics and narrative depth. Deixis, a key concept in pragmatics, connect language to specific context, including personal, spatial, and temporal. The study uses a qualitative descriptive approach to analyze how personal pronoun like “I” and “You” reflect relational conflict, spatial terms such as “home” and “away” convey emotional distance, and temporal markers like “when” and “ever” highlight shift in time and emotion. Finding reveal that deixis enriches the song’s emotional resonance, capturing themes of heartbreak, self-discovery, and emotional liberation. By exploring deixis in this song, this research contributes to understanding how linguistic elements enhance narrative and emotional expression in music.